Upaya Meningkatkan Pemahaman Bermain Bolavoli melalui Model Role Playing - Noerfalah, Dini; Lubay, Lukmannul Haqim; Budiman, Didin (TEGAR: Journal of Teaching Physical Education in Elementary School, 2019)
The purpose of this  research is to investigate how role playing method can improve student understanding in volleyball games activities. This research use class action research. The research used  in two cycle, every cycle have research action that done twice. The subject of this research is 30 students of level 5 class from one elementary school in Bandung. (12 boys, 18 girls). Role playing models combine with  GPAI instrument. Data is analyzed using percentage technic and  associated with games performance. This research showed that role playing models can improve student understanding in volleyball games. AbstrakPenelitian ini bertujuan untuk mengetahui apakah penerapan model role playing dapat  meningkatkan  pemahaman bermain siswa  dalam  bermain bolavoli.  Penelitian  ini  menggunakan  penelitian   tindakan   kelas.  Penelitian  dilakukan  dalam  dua  siklus,  setiap  siklus  dilaksanakan   sebanyak   dua kali tindakan penelitian. Subjek  penelitian  adalah  kelas  V  disalah  satu   sekolah dasar di Kota Bandung sebanyak 30 siswa (laki-laki: 12; perempuan:  18).  Model role playing dikombinasikan dengan instrument Game Performance Analisis Instrumen. Data dianalisis menggunakan teknik persentase dan dikaitkan dengan keterampilan bermain. Hasil penelitian menunjukan model pembelajaran role playing dapat meningkatkan pemahaman bermain bolavoli.